2004
DOI: 10.1101/gad.1234104
|View full text |Cite
|
Sign up to set email alerts
|

A conserved protein network controls assembly of the outer kinetochore and its ability to sustain tension

Abstract: Kinetochores play an essential role in chromosome segregation by forming dynamic connections with spindle microtubules. Here, we identify a set of 10 copurifying kinetochore proteins from Caenorhabditis elegans, seven of which were previously uncharacterized. Using in vivo assays to monitor chromosome segregation, kinetochore assembly, and the mechanical stability of chromosome-microtubule attachments, we show that this copurifying protein network plays a central role at the kinetochore-microtubule interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
515
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(538 citation statements)
references
References 37 publications
20
515
2
1
Order By: Relevance
“…NMS group proteins reassemble to the kinetochore during prophase and toward metaphase in meiosis, and subsequently DASH group proteins localize at the centromere during chromosome segregation. These groupings are generally consistent with the complex structures revealed by genetic interactions and proteomic analyses (De Wulf et al, 2003;Cheeseman et al, 2004;Obuse et al, 2004;Liu et al, 2005).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…NMS group proteins reassemble to the kinetochore during prophase and toward metaphase in meiosis, and subsequently DASH group proteins localize at the centromere during chromosome segregation. These groupings are generally consistent with the complex structures revealed by genetic interactions and proteomic analyses (De Wulf et al, 2003;Cheeseman et al, 2004;Obuse et al, 2004;Liu et al, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…Biochemical analyses have revealed that the kinetochore complex is comprised of subcomplexes of proteins. Many of these proteins are conserved in other eukaryotes, from yeasts to humans (De Wulf et al, 2003;Nekrasov et al, 2003;Cheeseman et al, 2004;Obuse et al, 2004;reviewed in Meraldi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the kinetochore structure in our model is specifically taken from the Dam1 ring complex in budding yeast (5)(6)(7). The kinetochore structure in other cells could be different from the ring-like geometry (35). In this aspect, this model could serve as a starting point for further investigations.…”
mentioning
confidence: 99%
“…This approach identified seven novel orthologous kinetochore proteins in mammals, three novel proteins in D. melanogaster and two novel proteins in plants. These results implied that most kinetochore proteins are conserved in eukaryotes, a finding that was confirmed by biochemical and genetic studies identifying those same proteins as bona fide kinetochore proteins (Cheeseman et al, 2004;Foltz et al, 2006;Obuse et al, 2004;Okada et al, 2006;Schittenhelm et al, 2007). The overall conclusion of these studies was that the core of eukaryotic kinetochores is composed of two large conserved protein networks: on one side the KMN network, which consists of Knl-1, the hetero-tetrameric MIND/Mis12 subcomplex, and the hetero-tetrameric-NDC80 subcomplex, and on the other side the CCAN network (Constitutive Centromere Associated Network, which is also called CENP-A NAC/CAD or CENP-H/I complex), which consists of 15 subunits.…”
Section: Kinetochores a Highly Conserved Structure Only At Second Lookmentioning
confidence: 55%